SUVARNABHUMI AIRPORT SERVICE QUALITY UNDER CORONAVIRUS 2019 CIRCUMSTANCES - Seksarn, Punnathorn; Pataragamonepong, Napapa; Moungsawad, Attapol (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2022)
The objective of this study was to investigate the perception of Thai passengers towards the quality of service at Suvarnabhumi Airport during the Coronavirus Disease 2019 (COVID-19) situation. This study employed a quantitative method using a survey with questionnaires to collect data from 400 Thai passengers, both males and females, aged over 18 years old, who had a domestic flight from Suvarnabhumi Airport at least once between February 2020 and February 2021. The results of this research revealed that the respondents had a high perception level of the service quality in every aspect, on an average of 4.03. When considered in each aspect, the perception level was also at a high level in terms of assurance on an average of 4.09, tangibles at 4.05, empathy at 4.03, reliability at 4.00, and responsiveness at 3.94, respectively. The hypothesis test results revealed that (1.) the difference in age and marital status indicated a statistically significant difference in the perception level of the service quality in terms of tangibles, reliability, responsiveness, and overall aspects with statistical significance at the 0.05 level. (2.) the difference in age indicated a statistically significant difference in the perception level of the service quality in terms of assurance and empathy with statistical significance at the 0.05 level.